Programme de Filets Sociaux Jigisemejiri: Midline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
In 2014 the Government of Mali began implementing its “Filets Sociaux (Jigisémèjiri)” program that aims at reducing poverty and improving human capital accumulation through targeted cash transfers, accompanying measures (or trainings), and preventive nutrition packages. In order to rigorously and independently assess the impacts of the program, the Government of Mali collaborated with research partners, International Food Policy Research Institute (IFPRI) and Institut de recherché pour le développement (IRD), to undertake an impact evaluation. The impact evaluation assesses how the “Jigisémèjiri” program impacts household welfare, and, in particular, household food consumption, food security, and dietary diversity, in addition to child nutrition and development. The impact evaluation is designed as a two-stage randomized control trial in which 96 communes were randomly assigned to begin receiving the program in 2014 or 2015 (early treatment) or in 2016 or 2017 (late treatment). Within a subset of the early treatment communes deemed eligible for nutrition packages, villages were randomly assigned to receive the nutrition packages or not receive them. This dataset is from the midline panel survey conducted in August–November 2016, before the late treatment was rolled into the program.